1998
DOI: 10.1038/sj.bjp.0702135
|View full text |Cite
|
Sign up to set email alerts
|

A partial involvement of histamine in ultrasonically nebulized distilled water‐induced bronchoconstriction in guinea‐pigs

Abstract: 1 Inhalation of ultrasonically nebulized distilled water (UNDW) can induce bronchoconstriction only in asthmatics, but mechanisms of the response are not well known. We recently reported a guinea-pig model of UNDW-induced bronchoconstriction (UNDW-IB) in which UNDW induces bronchoconstriction when UNDW is inhaled 20 min after a challenge with aerosolized ovalbumin (OA) in passively sensitized, anaesthetized and arti®cially ventilated guinea-pigs. 2 To elucidate the role of histamine in the UNDW-IB, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This result suggests that aminophylline m ay keep it s bronchodilator activity even in b -blockade state. A tropine giv en 15 m in utes after antigen challenge did not reduce the antigen-induced increase in the P ao or prevent the distilled waterinduced bronchoconstriction [ 21] or PI B, w hereas it did reduce antigeninduced bronchoconstriction w hen administered before the antigen challenge. I t is speculated that cholinergic innervation m ay be decreased by antigeninduced bronchoconstriction, but it is possible that anesthesia becom es deeper w ith tim e. W e do not know the exact reason for the ab sence of eÚ ect of atropine on PI B in our guinea pigs model.…”
Section: Discussionmentioning
confidence: 87%
“…This result suggests that aminophylline m ay keep it s bronchodilator activity even in b -blockade state. A tropine giv en 15 m in utes after antigen challenge did not reduce the antigen-induced increase in the P ao or prevent the distilled waterinduced bronchoconstriction [ 21] or PI B, w hereas it did reduce antigeninduced bronchoconstriction w hen administered before the antigen challenge. I t is speculated that cholinergic innervation m ay be decreased by antigeninduced bronchoconstriction, but it is possible that anesthesia becom es deeper w ith tim e. W e do not know the exact reason for the ab sence of eÚ ect of atropine on PI B in our guinea pigs model.…”
Section: Discussionmentioning
confidence: 87%
“…Histamine involvement was observed in a guinea pig model of UNDW-induced bronchoconstriction [7], suggesting a role for mast cell degranulation in this phenomenon. Protein concentration in the BALF increased significantly in T. canis-infected mice at 14 and 28 days p.i.…”
Section: Discussionmentioning
confidence: 93%
“…At 24 days p.i., UNDW inhalation increased histamine release into BALF from the T. canis-infected group above the levels found in the infected group that had not received inhalation. In fact, it has also been suggested that inhalation of UNDW could lead to mast cell lysis and histamine release [5,7] and consequently induce protein extravasation. In vitro studies have demonstrated that mast cells can release histamine when exposed to hypotonic solutions [6,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some researchers reported that alpha‐adrenergic agonists enhance mediator release ( Kaliner, Orange & Austen, 1972) and others studied the correlation between alpha‐adrenoceptor and mucus secretion ( Ueki, German & Nadel, 1980). Therefore, we hypothesized that differences of mediator mechanisms in pathogenesis of bronchial asthma may be one of the reasons for the conflicting results ( Songür et al , 1994 ; Songür et al , 1995 ; Fujimura et al , 1996a,b,c, 1998a,b ; Yoshiwara et al , 1996 ).…”
Section: Discussionmentioning
confidence: 99%